2011
DOI: 10.1089/neu.2011.1864
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Improves Functional Outcomes, Memory Deficits, and Histopathology after Endovascular Perforation-Induced Subarachnoid Hemorrhage in Rats

Abstract: Subarachnoid hemorrhage (SAH) results in significant long-lasting cognitive dysfunction. Therefore, evaluating acute and long-term outcomes after therapeutic intervention is important for clinical translation. The aim of this study was to use minocycline, a known neuroprotectant agent, to evaluate the long-term benefits in terms of neurobehavior and neuropathology after experimental SAH in rats, and to determine which neurobehavioral test would be effective for long-term evaluation. SAH was induced by endovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 57 publications
2
70
3
Order By: Relevance
“…5 Similar findings were reported by two other groups using an endovascular perforation model of SAH. 21,23 The discrepancy between our studies may be due to differences in methods. In the current study, rats were housed in an intensive care incubator (at 261C, with easily accessible soft food and water for 48 hours) before their return to a room temperature cage.…”
Section: New Findingsmentioning
confidence: 58%
See 1 more Smart Citation
“…5 Similar findings were reported by two other groups using an endovascular perforation model of SAH. 21,23 The discrepancy between our studies may be due to differences in methods. In the current study, rats were housed in an intensive care incubator (at 261C, with easily accessible soft food and water for 48 hours) before their return to a room temperature cage.…”
Section: New Findingsmentioning
confidence: 58%
“…1 In other studies, rats with SAH did have cognitive/memory dysfunction up to 5 weeks after ictus. [21][22][23] Mechanism of Long-Term Potential Loss in Subarachnoid and Other Neurologic Diseases Our previous study showed that the induction phase of LTP did not change after SAH but that the maintenance phase of LTP was diminished. 6 This suggests that the molecular machinery for induction of LTP such as N-methyl-D-aspartate (NMDA) receptors is intact, but the molecular components for maintenance of LTP such as a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic (AMPA) receptors and their associated trafficking, CamK-II activation, and other downstream processes, are impaired.…”
Section: New Findingsmentioning
confidence: 99%
“…This is a major experimental limitation, as it is by far the most commonly utilized mouse model of SAH owing to its relative ease in development, close recapitulation of the physiologic events involved with aneurysmal SAH (e.g., arterial perforation, localization of blood in the basal cisterns, acute rise in intracranial pressure, and transient global ischemia), and applicability to the use of powerful, targeted genetic manipulations. We rigorously examined possible reasons for our finding, including high mortality (albeit comparable to the 20% to 33% reported in rat studies 16,[18][19][20], lack of sensitivity of the MWM protocol, and extent of neuronal cell loss in hippocampal CA1. We increased survival by modifying postoperative support; moreover, we employed different MWM protocols, the standard Place task and the more sensitive Learning Set task.…”
Section: Discussionmentioning
confidence: 86%
“…14 Experimental SAH research has thus sought to model long-term neurobehavioral outcomes and elucidate the mechanisms responsible. Morris water maze (MWM) deficits have been documented in all three principal rat models 3 to 5 weeks after SAH, [15][16][17][18][19][20] along with T-maze deficits in endovascular perforation SAH; 19 moreover, treatment with statins 17 and minocycline 19 has decreased SAHinduced cognitive deficits. Notably, a strong correlation was seen in rat SAH between MWM performance and neuronal cell counts in hippocampus at 5 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated that minocycline improves outcomes and protects against early brain injury through MMP-9 inhibition after SAH [22]. Furthermore, early minocycline treatment after SAH provides long-term benefits with respect to cognitive function and improved histopathology [23]. However, the anti-inflammatory and anti-apoptotic effects of minocycline and the potential mechanisms underlying these effects have not been evaluated in EBI after SAH.…”
Section: Introductionmentioning
confidence: 99%